LỰA CHỌN SẢN PHẨM SƠN BẢO VỆ THÉP PHÙ HỢP VỚI CÁC VÙNG KHÍ HẬU NHIỆT ĐỚI - Chử, Minh Tiến (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
CHOOSING STEEL PROTECTION PAINT PRODUCTS SUITABLE FOR TROPICAL CLIMATE AREAThis article presents the results of natural testing at 3 test stations of the Vietnam-Russia Tropical Center for a period of 5 years on common paint systems with the evaluation criterion being the coating's ability to protect against corrosion. Research shows that the tropical durability of the product depends on two groups of factors: the nature of the coating systems and the conditions of use. According to the nature of the paint system, the durability of the paint systems decreases in series: PU paint > AC paint > EP paint > AK paint. According to the conditions of use, the durability of paint systems decreased according to the test locations: Hoa Lac > Can Gio > Dam Bay. The research results have high practical value, and are guidelines for choosing paint products suitable for use conditions.